2015
DOI: 10.1186/s40248-015-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

Research on psychosocial aspects of asthma in the Arab world: a literature review

Abstract: The importance of psychosocial factors in the management of bronchial asthma has long been recognized. This paper offers a review of research published in the English language related to psychosocial aspects of bronchial asthma in Arab countries. Several databases (PubMed, Science Direct, Springer Link, ERIC, and PsychInfo) were searched using the following keywords: bronchial asthma, Arab countries, Algiers, Bahrain, Comoros, Djibouti, Egypt, Iraq, Jordan, Kuwait, Lebanon, Libya, Mauritania, Morocco, Oman, Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…1 Asthma control factors in the GCC countries (Review 1): Flow diagram of search strategy/approach. SLR: Systematic Literature Review; GCC: Gulf Cooperation Council [ 31 – 36 ] …”
Section: Methodsmentioning
confidence: 99%
“…1 Asthma control factors in the GCC countries (Review 1): Flow diagram of search strategy/approach. SLR: Systematic Literature Review; GCC: Gulf Cooperation Council [ 31 – 36 ] …”
Section: Methodsmentioning
confidence: 99%
“…Female gender, older age, obesity, comorbid diseases such as depression, are prognostic factors associated with poor QoL ( 11 , 16 , 17 ). Poor QoL in asthmatic patients is associated with detrimental consequences resulting in a high prevalence of behavioral and emotional difficulties, depression, and poor academic performance ( 18 ). Moreover, avoiding triggers of asthma, and enhancing patient QoL, are effective measures to reduce morbidity and mortality ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was a study which had been done in Nigeria concluded that around a quarter of the children attending asthma clinic were psychologically affected beside the interference of asthma with the daily activities [11]. In the Arab world, many studies revealed that psychosocial aspects of asthma had a significant adverse impact on the quality of life of children [12].…”
Section: Introductionmentioning
confidence: 99%